Diversity recovery and probiotic shift of gastric microbiota in functional dyspepsia patients after Helicobacter pylori eradication therapy - Wang, Wenxue; Liu, Zhongjian; Zhang, Yu; Guo, Zhiping; Liu, Jieyu; Li, Siyun; Huang, Jihua; Geng, Jiawei; Zhang, Fan; Guo, Qiang (Frontiers in Microbiology, 2023)
The effects of Helicobacter pylori eradication on gastric mucosa-colonizing microbes in patients with functional dyspepsia (FD) remain unclear. Here, we explored microbial variation induced by H. pylori infection and eradication treatment in FD patients.Gastric microbial abundance and diversity were significantly reduced in the H. pyloriinfected FD patients. Eradication treatment increased alpha and beta diversity of gastric mucosa-colonizing microbes, and promoted the expansion of several probiotic microbes, such as Leuconostoc mesenteroides, which exhibited a matched antagonistic performance against H. pylori. Significant variation was observed in gastric mucosacolonizing microbes between H. pylori-positive and H. pylori-negative FD patients.Eradication treatment induced microbial diversity recovery and may provide sufficient nutrition and space for probiotic microbes, such as Leuconostoc mesenteroides.